Expansion potential of skin grafts with novel I-shaped auxetic incisions. (7th December 2021) - Gupta, Vivek; Chanda, Arnab
Abstract: Severe burn injures lead to millions of fatalities every year due to lack of skin replacements. While skin is a very limited and expensive entity, split thickness skin grafting, which involves the projection of a parallel incision pattern on a small section of healthy excised skin, is typically employed to increase the expansion and cover a larger burn site. To date, the real expansion capacity of such grafts are low (<3 times) and insufficient for treatment of severe burn injuries. In this study, novel I-shaped auxetic incision patterns, which are known to exhibit high negative Poisson's ratios, have been tested on the skin to investigate their expansion potential. Fourteen two-layer skin graft models with varying incision pattern parameters (i.e., length, spacing, and orientation) were developed using finite element modelling and tested under uniaxial and biaxial tensile loads. The Poisson's ratio, meshing ratios, and induced stresses were quantified across all models. Graft models tested uniaxially along the orthogonal directions indicated opposite trends in generated Poisson's ratios, as the length of the I-shape incisions were increased. Biaxially, with a symmetric and closely spaced I-shape pattern, graft meshing ratios up to 15.65 were achieved without overstressing the skin. Overall, the findings from the study indicated that expansion potentials much higher than that of traditional skin grafts can be achieved with novel I-shaped auxetic skin grafts, which would be indispensable for covering large wounds in severe burn injuries.